2022
DOI: 10.1155/2022/2970496
|View full text |Cite|
|
Sign up to set email alerts
|

Exploration and Research on Smart Sports Classrooms in Colleges in the Information Age

Abstract: Smart classrooms, made possible by the growing use of Internet information technology in the sphere of education, as one of the important foundations for the realization of smart education, have become the current hot direction of the development of educational information innovation and intend to propose some ideas and directions for smart sports teaching research in IA colleges and universities. The smart classroom is an intelligent and efficient classroom created by the “Internet +” way of thinking and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Exploratory research attempts to discover something new about a research topic and helps develop a rich understanding of research questions and findings (Lavigne et al, 2020;Elman et al, 2020). Multiple studies also adopt the exploratory approach when tackling topics related to smart classrooms because of the novelty or new expectations involved (Zhang et al, 2022;Jia, 2022;Petchamé et al, 2021). The approach assists the researcher to understand the forces that facilitate the occurrence of the phenomena observed in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploratory research attempts to discover something new about a research topic and helps develop a rich understanding of research questions and findings (Lavigne et al, 2020;Elman et al, 2020). Multiple studies also adopt the exploratory approach when tackling topics related to smart classrooms because of the novelty or new expectations involved (Zhang et al, 2022;Jia, 2022;Petchamé et al, 2021). The approach assists the researcher to understand the forces that facilitate the occurrence of the phenomena observed in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from recent years show a growing trend in classroom reconstruction based on the attributes of smart applications, smart technology, and smart management (Song et al, 2014). Among the technologies gaining popularity in the education sector include technologically advanced devices and intelligent systems, mobile and web applications, connectivity, data analysis and decision support, cybersecurity, storage and backup, and content management systems (Li-Shing et al, 2019;Cebrián et al, 2020;Zhang et al, 2022). Underpinning this shift are proposals for the creation of a physical space that is richly interwoven with actuators, sensors, displays, and computational elements that are embedded seamlessly and connected through a continuous network (Jun & Hong, 2014;Liu et al, 2017;Kwet & Prinsloo, 2020).…”
Section: Smart Classrooms In Education: a Backgroundmentioning
confidence: 99%
“…The rapid development of information network technology, computer technology, and internet technology has been integrated into various fields of society, providing new opportunities for transforming teaching modes in universities [ 1 , 2 ]. Nowadays, the concept of educational informatization has gained wide recognition and attention.…”
Section: Introductionmentioning
confidence: 99%
“…Applied Bionics and Biomechanics has retracted the article titled “Exploration and Research on Smart Sports Classrooms in Colleges in the Information Age” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Applied Bionics and Biomechanics has retracted the article titled "Exploration and Research on Smart Sports Classrooms in Colleges in the Information Age" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%